Perancangan Sistem Informasi Persediaan Obat pada Klinik Ibnu Sina Medika - Nabela, Harlinda Rasvi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Clinics as one of the providers of public health services require an appropriate and reliable information system, as well as adequate to improve the quality of health services to patients. Drug inventory is an important part of a clinic's health service system. Ibnu Sina Medika Clinic is one of the clinics in Kendal that still implements a manual stock recording system using paper and pen. This study aims to design a drug inventory system at the clinic to assist in managing drug stock, the Economic Order Quantity method is applied to complete the system. An information system is created that can produce output for calculating safety stock, reorder point, and EOQ, then a restock notification will appear if the drug stock has reached the reorder point limit.